2018
DOI: 10.3389/fmicb.2018.02400
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Procedure for Identification and Antifungal Susceptibility Testing of Yeasts From Positive Blood Cultures

Abstract: The development of rapid diagnostic assays for the identification and analysis of antimicrobial resistance of fungal pathogens causing invasive mycoses is of utmost importance to reduce morbidity and mortality. We evaluated the performance of a novel rapid procedure directly applied to monomicrobial blood cultures from patients with bloodstream infection caused by yeast species, including nine Candida and three non-Candida species. For the rapid procedure herein developed, samples of positive blood cultures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…What's more, we have been able to successfully identify 60% of fungi from blood cultures with extra extraction, which is higher than some studies (Vecchione et al, 2018;Azrad et al, 2019;Wu et al, 2019). It has been reported that the cut-off value could be lowered down to 1.400 without compromising accuracy (Lagace-Wiens et al, 2012;Saffert et al, 2012;Simon et al, 2019).…”
Section: Discussionmentioning
confidence: 70%
“…What's more, we have been able to successfully identify 60% of fungi from blood cultures with extra extraction, which is higher than some studies (Vecchione et al, 2018;Azrad et al, 2019;Wu et al, 2019). It has been reported that the cut-off value could be lowered down to 1.400 without compromising accuracy (Lagace-Wiens et al, 2012;Saffert et al, 2012;Simon et al, 2019).…”
Section: Discussionmentioning
confidence: 70%
“…However, in some instances, lowering the cut-off value may allow for rapid and correct microbial identification from samples resulting sub-optimal for MALDI-TOF MS analysis. For example, several authors [3134] observed that cut-off values could be lowered down to some extent without compromising accuracy for MALDI-TOF MS identification of microorganisms recovered from positive BCs, which possibly contain residual blood components affecting the quality of spectra. In the present study, the quality of spectra and, hence, identification scores might be affected by the presence in the sample for MALDI-TOF MS analysis of residual blood components deriving from positive BCs and/or microbial cell material of counter-selected microorganisms after enrichment of the selected microbial species in liquid media.…”
Section: Discussionmentioning
confidence: 99%
“…En règle générale, il s'agit d'une culture en milieu solide, sur gélose Sabouraud ou sur un milieu chromogène, mais la plupart des milieux de cultures peuvent convenir, y compris les géloses utilisées en bactériologie. L'identification à partir des hémocultures est possible [83,84] mais requiert des étapes de lavages et de purification qui obèrent la généralisation de son utilisation en routine. La paroi des champignons étant plus difficile à rompre que celle de la plupart des bactéries, il est nécessaire de réaliser un traitement chimique avant de mettre en oeuvre la technique de Maldi-TOF MS. Pour les levures, les premières études menées entre 2010 et 2011 avaient conclu que l'identification de la colonie sans extraction préalable donnait des spectres de qualité nettement inférieure à ceux obtenus avec une méthode d'extraction complète en tube à l'aide d'acide formique et d'acétonitrile [82,85,86].…”
Section: Identification Des Levures Et Champignons Filamenteux Par Spectrométrie De Masseunclassified